Methods and Applications of Inversion - Hansen, Per Christian; Jacobsen, Bo Holm; Mosegaard, Klaus (Springer Berlin Heidelberg, 2000)
This collection of conference papers describes state-of-the-art methodologies and algorithms used in the treatment of inverse problems, focusing on seismology and image processing. The papers also describe new general methodologies for analysis and solution of inverse problems by means of statistical and deterministic algorithms. The book gives a glimpse of recent techniques, many of which are still under development
Keywords: Earth Sciences; Geophysics/Geodesy; Geology; Atmospheric Sciences; Oceanography; Earth Sciences, general; Earth sciences; Geophysics; Atmospheric sciences; Inversionstheorie; Geophysik; Konferenzschrift -- 1998 -- Kopenhagen